Factors that influence MSMEs to Report Taxes - Damayanti, Prisila; Prihanto, Hendi (Atestasi : Jurnal Ilmiah Akuntansi, 2024)
The research aims to determine and analyze the response of taxpayers (taxpayers) in reporting their taxes in the post-Covid 19 pandemic era after the government provided various relief policies through tax incentives to entrepreneurs and MSMEs in terms of the aspects of taxpayers' literacy knowledge, set tax rates, profitability of taxpayers' businesses, and business opportunities faced now and in the future. The research was conducted on several MSME cafe entrepreneurs in the Jagakarsa - Ciganjur sub-district and surrounding areas as a population, using a questionnaire with a rolling snowball distribution technique based on information obtained during the survey to obtain a total of 110 samples. Data analysis uses Smart PLS statistical software with tests such as validity and reliability, inner and outer models, statistical t-hypothesis testing, multiple regression, and coefficient of determination—the results of the research state that not all of the hypotheses can be accepted. Taxpayers' knowledge of tax literacy and profitability obtained by taxpayers from MSME actors has a significant positive effect on the contribution of taxpayers' tax reporting so that the hypothesis is accepted, while tax rates through incentives set by the government and business opportunities from MSMEs are not has a significant effect on the contribution to tax reporting by MSME taxpayers so that the hypothesis is rejected.